Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan dan Pengemasan Diversifikasi Produk Berbasis Tepung Kaopi - Sri Wahyuni; Sarinah Sarinah; Rosnawintang Rosnawintang; Asnani Asnani; Arby'in Pratiwi (STKIP Andi Matappa, 2022)
This activity is a service activity by empowers the community with the aim of increasing economic value and making product diversity. Activities were carried out on the diversification of cocoa flour-based products. The method used in this product creation activity is to adjust the needs in the field, as is the case with how to create products according to the tastes and needs of consumers. As for the diversity that can be made according to needs, such as brownies, Roti Jala, Cookies, and Pizza. The manufacture of these products is always carried out on product diversification development. This method will give a high value to the selling price of the product produced. Community empowerment techniques are carried out through training and product manufacturing processes. In addition, training was also carried out on the packaging. The purpose of this training is to increase the knowledge and skills of the people who are fostered in this empowerment. This activity gives good results because it can diversify products from cocoa flour and have an impact on increasing income. Moreover, this activity was carried out during this pandemic, so that the development of diversified products made from local cocoa food raw materials would have a positive impact on the economic value of the community. This activity ends with an organoleptic test on the product which includes aroma, taste, and texture. The technique is done by providing cake ingredients per product and equipment assistance to 1 selected participant in the activities carried out.